1999
DOI: 10.1007/s007840050086
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of cast gold inlays and partial crowns - a retrospective study at a dental school clinic

Abstract: From 1963 to 1993, 890 patients were treated with 3518 cast gold restorations by students and postgraduate dentists. The longevity of these restorations was studied retrospectively using the patient files. Longevity was calculated using the method described by Kaplan and Meier. After the observation period, 111 (3.2%) of the examined restorations were not in place anymore. The most frequent reasons for failure were caries (33.7%), lack of retention (32.7%), endodontic treatment (29.6%), insufficient marginal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 12 publications
2
31
2
Order By: Relevance
“…The value for partial crowns was 86.1% and 85.7% for all restorations. 15 The latter value is exactly the same as that of the current study after 10 years.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The value for partial crowns was 86.1% and 85.7% for all restorations. 15 The latter value is exactly the same as that of the current study after 10 years.…”
Section: Discussionsupporting
confidence: 81%
“…Seventy-four patients, including 226 Cerec restorations, participated in the follow-up examination. Reasons for non-participation were relocation (15), death (2) and personal reasons (4). All examinations were performed by a single operator, despite that dentist not being the same one who had inserted the restorations.…”
Section: Methodsmentioning
confidence: 99%
“…It is between 68 and 97% for a ten-year period. 20,25,26 This corresponds to the range given for ceramic inlays, as well. 8,9,11,[16][17][18]27,28 When making this comparison, however, it must be noted that the observation period and the functional period in many cases do not yet cover a ten-year period when ceramic inlays are involved.…”
Section: Discussionmentioning
confidence: 94%
“…For this reason, the Kaplan-Meier method is regarded as being able to deliver more accurate estimates for the survival probability than the actuarial life table method 24 and is applied in numerous dental restoration studies. [8][9][10][11][16][17][18]20,21,25,26 Especially in large treatment centers, there are two reasons that the retrospective evaluation of patients' cards presents the risk of overlooking a substantial portion of interesting cases. For one thing, it can be difficult to recover all interesting cases and for another, the patients' cards may, for whatever reasons, be unavailable at the time of evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…8 Retrospective studies have revealed differences among survival rates for different partial preparation designs. [7][8][9][10][11] It is recommended when comparing the results of such research to review the survival probability of each type of preparation design separately and under definite conditions. 1 Cements seem to play a key role in achieving durable restorations.…”
Section: Introductionmentioning
confidence: 99%